Development Of Web-Based Learning Evaluation Tools in Vocational High Schools - Muhammadiah, Mas'ud; Wahab, Abdul; Surahman, Susilo; Cakranegara , Pandu Adi; Nduru , Maria Purnama (Sinkron : jurnal dan penelitian teknik informatika, 2022)
The use of school information systems that still use manual means in terms of learning evaluation makes it difficult in terms of assessment. This article will explain how to design a web-based school evaluation system at a vocational school. In this study, the methods used are research and development methods and data retrieval methods by making observations and interviews. The results of the final product research learning evaluation tool can be used in vocational schools and can facilitate schools in making learning evaluation tools. Development and research results can then be concluded that the process of developing web-based learning evaluation tools consists of assessment, design, development, implementation, and evaluation. Product results in the form of web-based learning evaluation tools. Based on the tests conducted, the development of web-based learning evaluation tools on aspects of software engineering, learning media, and visual communication can be categorized as very feasible, so this learning medium can be used as a learning medium to help the learning process. Based on the results of field tests, students' responses to web-based learning evaluation tools from the motivational aspect get a percentage of 81.94% (category "Very Good"), gain with a percentage of 83% (category "Very Good"), and convenience with a percentage of 76.61% (the category of "Very Good"), and usefulness with a percentage of 83.65% (category "Very Good"), and when on average get a percentage of 76.61% categorized as "Good".